Cyclophilin A and EMMPRIN (CD147) in cardiovascular diseases. (11th February 2014) - Seizer, Peter; Gawaz, Meinrad; May, Andreas E.
Abstract: Cyclophilin A (CyPA) is an abundantly expressed intracellular protein. It exerts a variety of functions due to its peptidyl–prolyl cis – trans isomerase (PPIase) activity. When released into the extracellular space, CyPA binds to its extracellular receptor CD147 (EMMPRIN) and thereby initiates a cascade of inflammatory processes. Recent data indicate that both extra- and intracellular CyPA significantly contribute to cardiovascular inflammation, myocardial ischaemia and reperfusion injury, and myocardial remodelling processes. Thus, CyPA appears to represent a novel target to treat vascular and myocardial inflammation.